Diagnóstico ambiental da área do aterro sanitário do Município de Cascavel - Rowe Junior, Elmo (2007)
This present research was developed in the State University of the West of Paraná - Unioeste - using the area of Cascavel s Sanitary landfil for the obtaining of coming data of contamination of the disposition of solid residues. Being like this monitoring the flow of originated pollutants of the sanitary landfil, through a conjugated diagnosis being used of soil analyses (done through located perforations along the area of the embankment), quality of the leachate (before and after-treatment) and monitorament system of groundwater, it can verify the efficiency of the drainage system, base impermeabilization and leachate treatment, pointing the points where the same ones can be being operated in a deficient way. The experiment was driven in field, being used an area of 7056 m2 jusant of the deposit of solid residues, where are located the system of leachate treatment and the monitorament system of groundwater. To characterize the leachate and the groundwaters, 4 collections of each point were accomplished, where the following parameters were verified: pH, Electric Conductivity, DBO, DQO and heavy metals (Hg, Zn, Cd, Ni, Cr and Ass). Soil samples were collected, of meter in meter, until the final depth of 5 meters, totaling 375 samples. The samples then were taken to the laboratory where they took place the pH, electric conductivity and organic matter, measurements, being generated later the maps of contamination to each depth, using the software SURFER32. The obtained results demonstrate that the leachate of the sanitary embankment of Cascavel, possesses high organic load and low levels of contamination for heavy metals. The maps of contamination generated for each depth demonstrate clearly the places where the leachate had higher influences in the quality of the soil. It is also verified larger variation levels in the pH and of electric conductivity of the soil in the close areas to the embankment, and smaller variations in the close areas to the monitorament system. As for the groundwaters, the system of monitorament of the embankment is possibly committed due to the contamination for superficial waters.